Stategi Penerapan Metodologi Pembelajaran PAI dalam Meningkatkan Budaya Religiusitas Siswa-Santri di TPQ Roudlotul Janah Gantang Baru Boboh Menganti Gresik Jawa Timur - Abdul Mu'id (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2019)
The Al-Quran Education Park Education Institute, (TPQ) Roudlotul Jannah Gantang Baru Boboh Menganti Gresik, East Java, is an educational forum designed to conduct studies and foster Al-Qur'an education taught by several experienced and competent teachers. To realize the ideals of deepening the values ??of the Qur'an, it is necessary to create a container called the Al-Qur'an Education Park. So that a container called Roudlotul Jannah Education Park was realized. The hope of the TPQ Management, the people of Gantang Baru hamlet is not to be unable to read the Al-Qura'an, because the best inheritance for our children is to recite, understand, and be able to read the Al-Quran fluently. and smooth. Religious tourism is part of a strategy to attract the interest of Santri guardians to entrust their children to be able to read the Qur'an at TPQ Roudlotul Jannah Gantang Baru Boboh Menganti.